Manajemen Konflik dan Stres di Sekolah - Fathorrahman, Fathorrahman (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2021)
Conflict is a conflict that occurs in the organization by members of the organization who seek to win their respective opinions and interests, while stress Stress can be interpreted as pressure, tension or unpleasant disturbances that come from outside a person. The purpose of this study was to determine: 1) the principal's efforts in managing conflict in schools, and 2) the principal's efforts in managing stress in schools. This research is a library research by collecting, analyzing books, journals, and previous research results that support the research theme. The findings in this study are as follows: in dealing with conflict and stress, a school principal must be able to identify the symptoms, the factors that cause it to occur. Furthermore, the principal makes a diagnosis of the conditions that are happening at that time, then takes actions through communications. The principal must act fairly and impartially to one party, let alone harm certain parties and benefit others. In dealing with conflict and stress, the principal must try not to become an element that exacerbates the conflicts that occur, the principal must not side with one element, on the contrary the leader must be in the middle to resolve conflicts or disputes that occur in the organization and school environment.